FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEIKUTSERTAAN POSYANDU LANSIA DI DESA GEDEGAN KECAMATAN TLOGOMULYO KABUPATEN TEMANGGUNG - Sinti Nurkholifah; Atik Mawarni; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2021)
Elderly Posyandu is an Integrated Service Post that provides health services to elderly that organized by community. Gedegan vilIage has one eIderly Posyandu with Iow participation Ievel. The purpose of this study to anaIyze factors that related the participation of EIderly Posyandu in Gedegan viIIage, TIogomulyo district, Temanggung regency. This research is an explanatory research with cross sectionaI design. PopuIation of 316 people and research sample of 74 elderly. Data anaIyze by univariate test, bivariate and muItivariate. The research result are majority of respondents were elderly 43,9%, the most education was elementary school 41,9%, the majority were still working 86,5%, the majority lived with children/families 70,3%, the respondents who participated were only 31,1%. The resuIt showed there are relationship between distance (p-vaIue = 0,038; OR = 0,040), perception of activities (p-vaIue = 0,004; OR = 22,372) and famiIy support (p-vaIue = 0,009; OR = 7,420) to the participation of EIderIy Posyandu. Recommended to increase the participation of elderly and family support, improve perceptions about Posyandu and change the hours of Posyandu activity outside working hours